PERAN UNITED NATIONS ENVIRONMENT PROGRAMME (UNEP) DALAM MELAKUKAN MITIGASI BENCANA HIDROMETEOROLOGI MELALUI ECO-DRR DI SUMATERA UTARA - Pandiangan, Della Adwina Rosuliana; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to explore the profile of the international environmental organization UNEP. It also seeks to examine the challenges Indonesia faces regarding hydrometeorological disasters on peatlands in North Sumatra. Furthermore, this research aims to explain UNEP's role in addressing environmental issues in Indonesia through the ECO-DRR program in North Sumatra. The research employs a qualitative approach, using secondary data collected through library research, sourced from books, journals, articles, and websites. The research utilizes a pluralism perspective and International Organization theory, which highlights UNEP as a key actor in this issue. According to the International Organization theory proposed by Pareira, international organizations play roles classified into three categories: Initiator, Facilitator, and Mediator. This research analyzes UNEP's role in disaster mitigation through ECO-DRR in North Sumatra. As a country with the largest tropical peatland area in the world, Indonesia faces inevitable disasters if its extensive peatlands are not properly managed. In recent decades, several hydrometeorological disasters, including fires, floods, and droughts, have become catastrophes for both local communities and the government. UNEP plays an active role in addressing peatland issues in North Sumatra as both an initiator and facilitator through the ECO-DRR program. A number of residents from Muara Manompas and Terapung Raya Villages have experienced the success of ECO-DRR mitigation in terms of material benefits and personal capacity. Keywords: UNEP, Peatland, Role, Hidrometeorology Disaster.